Analysis of Policy Implementation of Large-Scale Social Restrictions in the Administrative City of North Jakarta in 2021 - Kharis Nasution (International Journal of Social Service and Research, 2023)
The formulation of the problem in this research is how to implement, obstacles and efforts to optimize the implementation of the Large-Scale Social Restrictions (PSBB) policy in the Administrative City of North Jakarta. The purpose of this research is to find out and analyze the implementation, obstacles and efforts to optimize the implementation of the Large-Scale Social Restrictions (PSBB) policy in the Administrative City of North Jakarta. This study uses a post-positivism research paradigm with a qualitative descriptive method. In this study, there were 7 informants who were interviewed. The data analysis technique used is data reduction, data presentation and conclusion and verification. The results of this study concluded: (1) The implementation of the Large-Scale Social Restrictions (PSBB) policy in the Administrative City of North Jakarta, was carried out by forming the Covid-19 Task Force based on the Decree of the Governor of DKI Jakarta Province Number 1023 of 2020 concerning the Task Force for Handling Covid-19 in DKI Jakarta Province. The North Jakarta Administrative City Covid-19 Task Force also appealed to all people to implement health protocols by implementing 3M, namely wearing masks, washing hands and maintaining distance and avoiding crowds. As for people who violate the rules will be subject to strict sanctions. (2) Obstacles in the implementation of the Large-Scale Social Restrictions (PSBB) policy in the Administrative City of North Jakarta, include the low awareness and discipline of the community towards applicable regulations, as seen in the presence of places to eat that are open at night, places of worship that are still carrying out activities , the behavior of people who do not wear masks when outside the house, in crowds and so on. In addition, the minimal budget and the inadequate number of law enforcement and enforcement supervisors are factors hindering the optimal implementation of the PSBB policy. (3) Efforts that need to be made to optimize the implementation of the Large-Scale Social Restrictions (PSBB) policy in the Administrative City of North Jakarta, one of which is by forming a Task Force Team for the Acceleration of Handling Corona Virus Disease (Covid-19) consisting of various stakeholders to provide understanding and outreach to the public about the PSBB policy. Next is to fulfill the availability of infrastructure or supporting facilities for the implementation of the PSBB policy in handling Covid-19, such as the availability of masks, disinfectant fluids and also the availability of complete and adequate rapid test equipment. Another anticipatory step is preventive action from the government, especially the Ministry of Health, which cooperates with immigration in monitoring and preventing the entry of new viruses from outside to Indonesia through screening people who come to Indonesia.